EFEKTIVITAS PEMBELAJARAN SAINS MENGGUNAKAN STORYBOOK DIGITAL BERBASIS AUGMENTED REALITY DALAM KEMAMPUAN BERPIKIR KRITIS SISWA SD - Aurel Abelita Elsa Suroso; Cholifah Tur Rosidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the differences in students' critical thinking skills in science learning between those using digital storybooks and those not using AR-based digital storybooks. This type iof iresearch iis iquantitative iwith ian iexperimental method using a quasi-experimental design with a Posttest-only control group design, in which both groups are not given a pretest, but only a posttest after the treatment. The results of this study show a significant increase in the critical thinking skills of fifth-grade students in science learning. The average posttest score in the control class was 84, and after applying tthe AR-based digital storybook, The average post-test score in the experimental class increased to 91. thus, this AR- based digital storybook improved students' critical thinking outcomes in science learning after implementing the AR-based digital storybook.